Japanese Pharmacists' Perceptions of Self-Development Skills and Continuing Professional Development - Kayoko Takeda Mamiya; Kiyoshi Takahashi; Tatsuyuki Iwasaki; Tetsumi Irie (MDPI AG, 2023)
Background: The role of healthcare professionals, including pharmacists, is changing. Lifelong learning and continuing professional development (CPD) are more critical than ever for both current and future pharmacists in the face of global health challenges and new technologies, services and therapies that are continually and rapidly introduced into their daily practice. Currently, Japanese pharmacists' licences are not renewable, although most developed countries have a renewal system. Therefore, understanding Japanese pharmacists' perceptions of CPD is the first step in reviewing undergraduate and postgraduate education. Methods: The target population was Japanese pharmacists, i.e., community pharmacy pharmacists and hospital pharmacists. The participants were administered a questionnaire with 18 items related to continuing professional development. Results: Our study found that regarding item "Q16 Do you think you need further education in your undergraduate education to continue your professional development?", (a) the ability to identify one's own problems and issues, (b) the ability to make plans to solve problems and issues, (c) the ability to carry out plans to solve problems and issues and (d) the ability to repeat steps of self-development, approximately 60% of pharmacists answered that these aspects were "necessary" or "quite necessary". Conclusion: As part of universities' responsibility for the lifelong education of pharmacists, it is necessary to systematically conduct teaching seminars or undergraduate education or postgraduate education on self-development while training pharmacists to meet the needs of citizens.